FENOMENA MENIKAH MUDA DIKALANGAN REMAJA PEREMPUAN DI KELURAHAN PIPITAN - Suryani, Danik; Kudus, Wahid Abdul (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Marriage is an essential thing in the cycle of human life. Nowadays, the phenomenon of getting married at a young age is widespread in society. One of the reasons for marrying young is to avoid promiscuity that violates religious and social norms, besides reducing the burden on parents. Usually, couples who marry young generally have a high tolerance for change and mature more quickly than those involved in this study using a descriptive qualitative research method. The data collection techniques in this study were observation, interviews, and literature study. This research article aims to determine the phenomenon of young marriage among adolescent girls in Pipitan Village, Walantaka District, Serang City, Banten Province. The results of the research obtained in this article are (1) the driving factors of young marriage that occur among adolescent girls in Pipitan Village. (2) How does this young woman in Pipitan Village live her life as a wife. (3) Strategies used in overcoming problems related to their role as a young married couple. (4) What are the effects on young women in Pipitan Village who marry young.